2015
DOI: 10.2174/1874364101509010041
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography, Scanning Laser Polarimetry and Confocal Scanning Laser Ophthalmoscopy in Retinal Nerve Fiber Layer Measurements of Glaucoma Patients

Abstract: Purpose: To determine the correlations and strength of association between different imaging systems in analyzing the retinal nerve fiber layer (RNFL) of glaucoma patients: optical coherence tomography (OCT), scanning laser polarimetry (SLP) and confocal scanning laser ophthalmoscopy (CSLO).Materials and Methodology: 114 eyes of patients with moderate open angle glaucoma underwent spectral domain OCT (Topcon SD-OCT 2000 and Zeiss Cirrus HD-OCT), SLP (GDx VCC and GDx Pro) and CSLO (Heidelberg Retina Tomograph, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…As has been previously reported, the OCT showed the highest, whereas the HRT exhibited the lowest values for mean RNFL thickness (Fanihagh et al. 2015).…”
Section: Discussionsupporting
confidence: 77%
“…As has been previously reported, the OCT showed the highest, whereas the HRT exhibited the lowest values for mean RNFL thickness (Fanihagh et al. 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Diagnostic tools such as scanning laser polarimeter (GDx; Carl Zeiss Meditec, Dublin, CA), Heidelberg retina tomographer, and scanning laser ophthalmoscope are suitable for quantitatively assessing the NFL thickness, except the NFL thickness in the macula area. 11 Ocular coherence tomography (OCT) provides non-contact and non-invasive NFL thickness measurements and has become an essential clinical measure for objective glaucoma assessment. 12 Several authors have reported NFL thickness in normal children and adults as well as those with ocular anomalies.…”
Section: Nerve Fibre Layermentioning
confidence: 99%
“…1 This condition is characterised by progressive optic neuropathy, accelerated damage of the retinal ganglion cells and axons, and thinning of the retinal nerve fibre layer (RNFL) and neuroretinal rim. 2 Recent evidence suggests that loss of ganglion cells and anomalies of the RNFL occur before functional deficits become manifest in the visual fields. 3 Objective, quantitative and sensitive assessment methods of the RNFL thickness are therefore essential to diagnose and monitor progression of optic nerve diseases, such as glaucomatous optic neuropathy and other neurological causes.…”
Section: Introductionmentioning
confidence: 99%